7,7-Dimethyl-2-phenyl-6,7-dihydro[1,2,4]triazolo[1,5-a][1,3,5]triazin-5-amine. - Dolzhenko, Anton; Tan, G.; Koh, L.; Dolzhenko, A.; Chui, W. (Blackwell Munksgaard, 2007)
The title compound, C12H14N6, was synthesized via cyclocondensation of 5-guanidino-3-phenyl-1,2,4-triazole with acetone. Only one tautomeric form with the NH H atom vicinal to the methyl groups was observed in the crystal structure. The triazine ring adopts a flattened half-boat conformation. The dihedral angle between the triazole and phenyl rings is 9.99 (5). The crystal packing is stabilized by intermolecular N-H...N hydrogen bonds which link the molecules into a chain along the a axis.